A Consistent Metric for Performance Evaluation of Multi-Object Filters - Schuhmacher, D.; Vo, Ba Tuong; Vo, Ba-Ngu (IEEE, 2008)
The concept of a miss-distance, or error, between a reference quantity and its estimated/controlled value, plays a fundamental role in any filtering/control problem. Yet there is no satisfactory notion of a miss-distance in the well-established field of multi-object filtering. In this paper, we outline the inconsistencies of existing metrics in the context of multi-object miss-distances for performance evaluation. We then propose a new mathematically and intuitively consistent metric that addresses the drawbacks of current multi-object performance evaluation metrics.